El deber del Estado frente a la salud de los niños, niñas y adolescentes - Robles-Zambrano, Génesis Karolina; Rivera-Velasco, Luis Antonio; Santana-Muñoz, Ceslie Paulina (IUSTITIA SOCIALIS, 2021)
El deber del Estado frente a la salud de los niños, niñas y adolescentes